The goblin princess - Elliott, Rebecca (New York : Scholastic Inc., 2020)
Greta the goblin princess is bored, but when unicorns Bo and Sunny try to cheer her up by using their powers to make her queen (for a day), they discover just how much trouble a bored--and spoiled--goblin princess can cause for everyone around her.
3.0
K-3
590L
Keywords: Unicorns -- Juvenile fiction; Goblins -- Juvenile fiction; Magic -- Juvenile fiction; Princesses -- Juvenile fiction; Responsibility -- Juvenile fiction; Unicorns -- Fiction; Goblins -- Fiction; Magic -- Fiction; Princesses -- Fiction; Responsibility -- Fiction; Fantasy; Fantasy fiction